The Spice Girls - Golden, Anna Louise (New York Ballantine Books, 1997)
GIRL POWER!

After storming America with the might of a hurricane in January, the Spice Girls have become a British force to be reckoned with. After all, this fab five's first hit single, "Wannabe," shot to the top of the charts in thirty-five countries across five continents. Not too shabby for a once-struggling group of unknown artists.

Now here's the unauthorized book that dispels the rumors, squashes the innuendo, and lays it all out on the line. Did Mel B really work as a "private" dancer? Has Emma been known to streak in a hotel? And what happened to Geri's dress at the BRIT Awards? Find out the facts behind the phenomenon--and add a little spice to your life!
"The uncensored story behind pop's biggest phenomenon"--Cover and spine.
Includes bibliographical and electronic references (p. 214-215).
Gift.
Keywords: Spice Girls; Rock musicians -- England -- Biography; Women rock musicians -- England -- Biography